Microbial activity of iron-reducing bacteria and sulfate-reducing bacteria isolated from mine tailings in the presence of various electron donors - Rioux, Jean-Philippe (University of Ottawa (Canada), 2004)
Two abandoned mine tailings sites (Calumet near Ottawa, and Potter near Timmins, Ontario) have been shown to support active populations of iron- (IRB) and sulfate-reducing bacteria (SRB). The competition between IRB and SRB for similar electron donors was however never assessed. The present study looked into the potential competition between IRB and SRB isolated from those 2 sites since they represent different pH conditions and mineralogy. The Potter tailings are acidic to slightly acidic and contain large quantities of sulfides, whereas the Calumet tailings are alkaline and contain less pyrite and more carbonate minerals. Batch experiments were designed to test the competition between IRB and SRB for 3 electron donors (acetate, formate and lactate) and to determine the role of abiotic Fe(III) reduction. Results from abiotic systems indicated that Fe(II) was released overtime in the various systems due to the reduction of Fe(III)-rich minerals by the organic acids present in the medium and due to the chemical oxidation of pyrite by ferric iron. IRB could only grow in the Calumet systems containing inhibited SRB. In these systems, IRB growth was favored in the presence of acetate. In the systems containing active SRB, IRB growth was minimal in the presence of all electron donors, suggesting that they cannot compete with SRB under the conditions used in the systems. SRB present in all systems were capable of oxidizing all 3 electron donors, including acetate. Our results also showed that complete and incomplete lactate oxidizers were present in the Calumet and Potter systems.
Keywords: Geology.